Self-propagating reaction sintered magnesium aluminate spinel ramming material and preparation method thereof
By adopting a self-propagation reaction sintering process in the magnesium aluminum spinel ramming material, using the aluminum-thermal reaction of magnesium peroxide and metal aluminum, combined with the thermal conductivity of silicon carbide and silicon nitride, the problems of complex and high cost in the prior art are solved, and efficient and low-cost sintered products are achieved.
Patent Information
- Application Number
- CN202411823771.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The prior art When preparing silicon carbide-magnesium aluminum spinel composite refractory materials, the firing process is complex, the firing temperature is high, the fuel consumption is high, and the cost is high.
The magnesium-aluminum spinel strobe material is sintered by self-propagation reaction. Magnesium peroxide is used as the oxygen source to promote the aluminum-thermal reaction of metal aluminum. Combined with silicon carbide and silicon nitride as thermal conductors to quickly transfer heat, and dilute the activated alumina powder to avoid thermal stress collapse.
The sintering energy consumption has been reduced, the product has excellent performance, high volume density, high load softening temperature, significantly improved thermal shock stability, and significantly improved production efficiency and cost.
Smart Images

Figure BDA0005183721970000071 
Figure BDA0005183721970000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a self-propagating reaction sintered magnesia-alumina spinel ramming material and a preparation method thereof. Background Art
[0002] Magnesium aluminum spinel is a series of compounds with an equiaxed crystal system of MgAl2O4 molecular composition. Its unit cell consists of 32 cubic close-packed oxygen anions O 2- and A1 in 16 octahedral voids 3+ and 8 magnesium ions Mg in the tetrahedral voids 2+ The magnesium-aluminum spinel used in industry is artificially synthesized, with a hardness of more than 9.0 on the Mohs scale, a melting point of 2250°C, and a maximum operating temperature of 1900°C. This material is widely used in refractory materials due to its good resistance to slag erosion, thermal shock resistance, and high high-temperature strength.
[0003] Chinese patent CN107879753A discloses a silicon carbide-magnesium aluminum spinel composite refractory material, which uses silicon carbide particles as aggregate, uses fine powder or micropowder of magnesium aluminum spinel, aluminum oxide, and magnesium oxide as a matrix, and is added with an antioxidant; after the various raw materials are mixed and formed, they are dried and fired under charcoal or nitrogen atmosphere protection, and the maximum firing temperature is 1450-1600°C to obtain a composite refractory material with SiC as the main crystal phase and magnesium aluminum spinel as the secondary crystal phase.
[0004] Chinese patent CN111704466A discloses a silicon carbide-magnesium aluminum spinel-aluminum composite refractory material, which is mainly based on CN107879753A, and adds aluminum sol-coated metal aluminum powder with a particle size range of 10 to 45 μm and accounting for 2 to 8% of the total mass of the raw materials into the matrix. After machine pressing and forming, the green body is sintered at high temperature. When the metal aluminum powder is sintered at a maximum temperature of 1500 to 1600°C in a carbon-buried atmosphere, an Al-ONC fiber reinforcement phase is formed inside, which improves the room-temperature and high-temperature mechanical properties of the silicon carbide-magnesium aluminum spinel composite refractory material.
[0005] The above two methods both adopt high temperature sintering process in carbon buried or nitriding atmosphere to prepare silicon carbide-magnesium aluminum spinel composite refractory materials. The sintering process is complicated, the sintering temperature is high, the fuel consumption is large, and the cost is high. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a self-propagating reaction sintered magnesium-aluminum spinel ramming material and a preparation method thereof in view of the deficiencies in the prior art. The ramming material uses magnesium peroxide as an oxygen source to cause the metal aluminum to undergo an aluminothermic reaction to promote the sintering of the material, uses silicon carbide and silicon nitride as thermal conductors to quickly transfer the released heat, and uses alumina powder as a diluent to avoid thermal stress collapse caused by an overly intense reaction, thereby allowing the ramming material to be smoothly sintered through a self-propagating reaction, with low sintering energy consumption and excellent performance of the sintered product.
[0007] In order to solve the technical problem proposed by the present invention, the present invention provides a self-propagating reaction sintered magnesia-alumina spinel ramming material, comprising the following raw materials in parts by mass: 30 to 40 parts of spinel with a particle size of 3 to 6 mm, 5 to 15 parts of spinel with a particle size of 1 to 3 mm, 8 to 15 parts of magnesia sand with a particle size of less than 1 mm, 3 to 5 parts of silicon carbide with a particle size of less than 1 mm, 3 to 5 parts of silicon nitride powder, 2 to 5 parts of metallic silicon powder, 8 to 12 parts of activated alumina powder, 15 to 30 parts of magnesium peroxide powder, and 5 to 10 parts of metallic aluminum powder, the sum of the parts by mass of the above raw materials is 100 parts, and 1 to 2 parts of a liquid binder are added.
[0008] In the above scheme, the spinel is sintered spinel or fused spinel, and the sum of the Al2O3 and MgO contents thereof is ≥95%.
[0009] In the above scheme, the magnesia is dead-burned magnesia or fused magnesia, and the MgO content is ≥92%.
[0010] In the above scheme, the silicon carbide is black silicon carbide, and the SiC content is ≥98%.
[0011] In the above scheme, the silicon nitride powder is β-Si3N4, the Si3N4 content is ≥98%, and the particle size is 1 to 10 μm.
[0012] In the above scheme, the Si content of the metal silicon powder is ≥98%, and the particle size is 20 to 80 μm.
[0013] In the above scheme, the Al2O3 content of the activated alumina powder is ≥99%, the particle size is ≤10μm, and the median particle size D 50 0.5~1.5μm.
[0014] In the above scheme, the MgO2 content of the magnesium peroxide powder is ≥99.9%, the particle size is ≤10μm, and the median particle size D 50 0.5~1.5μm.
[0015] In the above scheme, the Al content of the metal aluminum powder is greater than 99%, and the particle size is ≤50 μm.
[0016] In the above scheme, the mass ratio of the magnesium peroxide powder to the metal aluminum powder is (3-3.2):1.
[0017] In the above solution, the liquid binder is a viscous liquid organic substance.
[0018] Furthermore, the liquid binder is one or more of tung oil, phenolic resin, tar, maltose, honey and the like.
[0019] The present invention also provides a method for preparing a self-propagating reaction sintered magnesia-alumina spinel ramming material, comprising the following steps:
[0020] 1) firstly, magnesium peroxide powder, metallic aluminum powder and a part of liquid binder are ball-milled and mixed once, then silicon nitride powder, metallic silicon powder and activated alumina powder are added and ball-milled for a second time, the obtained mixture is taken out and added into a blender, and then all the spinel, magnesia, silicon carbide and the remaining liquid binder are added and stirred evenly to obtain a ramming material;
[0021] 2) The ramming material is formed or pressed into bricks through a mold, dried naturally after demoulding, and then locally heated with a flame spray gun or laser to induce a thermite reaction to achieve self-propagating overall sintering.
[0022] In the above scheme, the ball milling is carried out under vacuum or inert atmosphere, the ball milling speed is 20-50 r / min, the first ball milling time is 1-2 h, and the second ball milling time is 2-3 h.
[0023] In the above scheme, the ball milling is carried out in a ball mill with a cooling device to ensure that the material temperature during the ball milling process is ≤60°C.
[0024] In the above scheme, the rotation speed of the stirrer is 30 to 45 r / min, and the stirring time is 30 to 60 min.
[0025] In the above scheme, the liquid binder is added twice, the first addition amount is 30-50% of the total mass, and the second addition amount is 50-70% of the total mass.
[0026] In the above scheme, the natural drying time is 12 to 36 hours.
[0027] In the above scheme, the temperature of the local heating is greater than 1250° C. and the time is 5 to 10 seconds.
[0028] In the above scheme, the bulk density of the ramming material after sintering is 2.95-3.05 g / cm 3 , apparent porosity 14.5 ~ 16.5%, room temperature compressive strength 70 ~ 100MPa, load softening temperature > 1680 ℃, 1100 ℃ water-cooled thermal shock stability 20 ~ 25 times.
[0029] The technical concept of the present invention is as follows:
[0030] Thermite reaction is a redox reaction between aluminum powder and metal oxides, and the reaction is violently exothermic. When the temperature exceeds 1250℃, the aluminum powder oxidizes violently, burns and releases a lot of heat. The temperature of this exothermic reaction can reach over 3000℃. Thermite reaction is very rapid, short in action time, and has self-propagating characteristics. If it can be used in magnesium-aluminum spinel ramming materials, it can significantly reduce sintering energy consumption. However, there are problems in it. In dense refractory materials, if thermite reaction is simply used, local overheating and heat cannot be smoothly discharged, which will cause the material to crack or even explode; in addition, the added metal oxides and the generated metal melting points are relatively low, which affects the performance of refractory materials. The present invention adopts magnesium peroxide as an oxygen source to generate magnesium oxide and aluminum oxide as refractory phases, and the spinel produced by magnesium oxide and aluminum oxide is also a refractory phase; activated alumina powder is used to dilute the thermite to reduce the reaction intensity, and the activated alumina powder can synthesize the spinel with the generated magnesium oxide; silicon carbide and silicon nitride are used as heat-conducting media to quickly transfer the released heat, maintain the uniform temperature of the entire construction body, and enable the entire construction body to smoothly self-propagate reaction to solve the above problems.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1) Magnesium peroxide is used as an oxygen source to make a thermite with metal aluminum powder. A thermite reaction occurs at >1250°C to generate aluminum oxide and magnesium oxide, which are further synthesized into spinel. At the same time, a large amount of heat is released. The heat is released through the material's own reaction to achieve the purpose of sintering.
[0033] 2) Silicon carbide and silicon nitride are used as heat-conducting media to evenly conduct the heat released by the reaction to the entire ramming structure, causing a self-propagating reaction and sintering the material inside and outside at the same time.
[0034] 3) Under the oxygen partial pressure generated by the decomposition of magnesium peroxide, metal aluminum powder, metal silicon powder and β-Si3N4 synthesize and grow Sialon whiskers along the β-Si3N4 needle-shaped crystals, and solid-solution connect with the surface of silicon carbide to form a network structure, further strengthening the material and improving thermal shock stability.
[0035] 4) Mixing the activated alumina powder with the thermite, diluting and dispersing the thermite, reducing the intensity of the thermite reaction, and avoiding material cracking due to excessive local temperature; at the same time, the activated alumina powder is in full contact with magnesium peroxide, and can react with magnesium oxide generated by the decomposition of magnesium peroxide to form evenly distributed spinel in situ in the matrix, resulting in a certain volume expansion, which compensates for the shrinkage of the raw materials due to the melting and sintering of the added powder at high temperature, and improves the density of the material.
[0036] 5) MgO on the surface of magnesia reacts with activated alumina to generate spinel, which directly combines with periclase in magnesia and spinel in the matrix, reducing the porosity and improving the strength of the material. DETAILED DESCRIPTION
[0037] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0038] In the following embodiments, the sintered spinel or fused spinel selected satisfies the sum of the Al2O3 and MgO contents ≥ 95%; the dead-burned magnesia or fused magnesia selected satisfies the MgO content ≥ 92%; the silicon carbide is black silicon carbide, with a SiC content ≥ 98%; the silicon nitride powder is β-Si3N4, with a Si3N4 content ≥ 98% and a particle size of 1 to 10 μm; the Si content of the metallic silicon powder is ≥ 98% and a particle size of 20 to 80 μm; the activated alumina powder is made by heating and dehydrating aluminum hydroxide, with an Al2O3 content ≥ 99%, a particle size ≤ 10 μm, and a median particle size D 50 0.5~1.5μm; MgO2 content of magnesium peroxide powder ≥99.9%, particle size ≤10μm, and median particle size D 50 The Al content of the metal aluminum powder is greater than 99%, and the particle size is ≤50μm.
[0039] Example 1
[0040] A self-propagating reaction sintered magnesia-alumina spinel ramming material comprises the following raw materials in parts by mass: 30 parts of fused spinel with a particle size of 3-6 mm (excluding 6 mm), 10 parts of fused spinel with a particle size of 1-3 mm (excluding 3 mm), 10 parts of dead-burned magnesia with a particle size of less than 1 mm, 3 parts of silicon carbide with a particle size of less than 1 mm, 5 parts of silicon nitride powder, 2 parts of metallic silicon powder, 8 parts of activated alumina powder, 24 parts of magnesium peroxide powder, 8 parts of metallic aluminum powder, and 2 parts of tar.
[0041] A method for preparing a self-propagating reaction sintered magnesia-alumina spinel ramming material comprises the following steps:
[0042] 1) First, 24 parts of magnesium peroxide powder, 8 parts of metal aluminum powder and 1 part of tar are placed in a ball mill, argon gas is filled into the ball mill for protection and the speed is adjusted to 20r / min, and the ball milling is mixed for 2h, and then 5 parts of silicon nitride powder, 2 parts of metal silicon powder and 8 parts of activated alumina powder are added to continue ball milling and mixing for 1h. During the ball milling process, the material temperature is ensured to be ≤60°C by a cooling device; the obtained mixture is taken out and added to a stirrer, and then 30 parts of fused spinel with a particle size of 3-6mm, 10 parts of fused spinel with a particle size of 1-3mm, 10 parts of dead-burned magnesia with a particle size of <1mm, 3 parts of silicon carbide with a particle size of <1mm and 1 part of tar are added, and stirred at 30r / min for 45min to obtain a ramming material;
[0043] 2) The ramming material is placed in a mold of 230 mm × 114 mm × 65 mm, and is pressed at 100 MPa. After demolding, it is naturally placed for 24 hours to dry, and then placed on alumina hollow spherical bricks. The laser igniter is used to focus and irradiate for 5 seconds to make the temperature of the irradiation point reach above 1250 ° C, which triggers the thermite reaction and realizes self-propagating overall sintering.
[0044] Example 2
[0045] A self-propagating reaction sintered magnesia-alumina spinel ramming material comprises the following raw materials in parts by mass: 32 parts of fused spinel with a particle size of 3-6 mm (excluding 6 mm), 8 parts of fused spinel with a particle size of 1-3 mm (excluding 3 mm), 12 parts of dead-burned magnesia sand with a particle size of less than 1 mm, 5 parts of silicon carbide with a particle size of less than 1 mm, 5 parts of silicon nitride powder, 4 parts of metallic silicon powder, 10 parts of activated alumina powder, 18 parts of magnesium peroxide powder, 6 parts of metallic aluminum powder, and 1 part of phenolic resin.
[0046] A method for preparing a self-propagating reaction sintered magnesia-alumina spinel ramming material comprises the following steps:
[0047] 1) First, 18 parts of magnesium peroxide powder, 6 parts of metal aluminum powder and 0.4 parts of phenolic resin are placed in a ball mill, argon gas is filled into the ball mill for protection and the speed is adjusted to 30r / min, and the ball milling is mixed for 1h, and then 5 parts of silicon nitride powder, 4 parts of metal silicon powder and 10 parts of activated alumina powder are added to continue ball milling and mixing for 2h. The material temperature is ensured to be ≤60°C by a cooling device during the ball milling process; the obtained mixture is taken out and added to a stirrer, and then 32 parts of fused spinel with a particle size of 3-6mm, 8 parts of fused spinel with a particle size of 1-3mm, 12 parts of dead-burned magnesia with a particle size of <1mm, 5 parts of silicon carbide with a particle size of <1mm and 0.6 parts of phenolic resin are added, and stirred at 35r / min for 60min to obtain a ramming material;
[0048] 2) Place the ramming material in a 160mm×40mm×40mm mold, ram it into a dense shape, leave it to dry naturally for 24 hours after demoulding, then place it on spinel sand, and use a flame spray gun to spray flame at a fixed point to make the local temperature reach 1250℃ and maintain it for 8s to induce thermite reaction and achieve self-propagating overall sintering.
[0049] Example 3
[0050] A self-propagating reaction sintered magnesia-alumina spinel ramming material comprises the following raw materials in parts by mass: 40 parts of sintered spinel with a particle size of 3-6 mm (excluding 6 mm), 5 parts of sintered spinel with a particle size of 1-3 mm (excluding 3 mm), 8 parts of fused magnesia with a particle size of less than 1 mm, 3 parts of silicon carbide with a particle size of less than 1 mm, 5 parts of silicon nitride powder, 2 parts of metallic silicon powder, 10 parts of activated alumina powder, 20 parts of magnesium peroxide powder, 7 parts of metallic aluminum powder, and 2 parts of tung oil.
[0051] A method for preparing a self-propagating reaction sintered magnesia-alumina spinel ramming material comprises the following steps:
[0052] 1) First, 20 parts of magnesium peroxide powder, 7 parts of metallic aluminum powder and 0.8 parts of tung oil are placed in a ball mill, and helium is filled into the ball mill for protection and the speed is adjusted to 40r / min, and the ball milling is mixed for 2h, and then 5 parts of silicon nitride powder, 2 parts of metallic silicon powder and 10 parts of activated alumina powder are added, and the ball milling is continued for 1h. The material temperature is ensured to be ≤60°C by a cooling device during the ball milling process; the obtained mixture is taken out and added to a stirrer, and then 40 parts of sintered spinel with a particle size of 3-6mm, 5 parts of sintered spinel with a particle size of 1-3mm, 8 parts of fused magnesia with a particle size of <1mm, 3 parts of silicon carbide with a particle size of <1mm and 1.2 parts of tung oil are added, and the mixture is stirred at 40r / min for 40min to obtain a ramming material;
[0053] 2) Place the ramming material in a mold of 230mm×114mm×65mm, press it into bricks with a brick press, leave it to dry naturally for 24 hours after demoulding, then place it on corundum sand, and use a flame spray gun to spray flames at fixed points to make the local temperature reach 1250℃ and maintain it for 8s, thereby inducing thermite reaction and achieving self-propagating overall sintering.
[0054] Example 4
[0055] A self-propagating reaction sintered magnesia-alumina spinel ramming material comprises the following raw materials in parts by mass: 36 parts of sintered spinel with a particle size of 3-6 mm (excluding 6 mm), 6 parts of sintered spinel with a particle size of 1-3 mm (excluding 3 mm), 8 parts of dead-burned magnesia sand with a particle size of less than 1 mm, 4 parts of silicon carbide with a particle size of less than 1 mm, 3 parts of silicon nitride powder, 3 parts of metallic silicon powder, 10 parts of activated alumina powder, 23 parts of magnesium peroxide powder, 7 parts of metallic aluminum powder, and 1 part of honey.
[0056] A method for preparing a self-propagating reaction sintered magnesia-alumina spinel ramming material comprises the following steps:
[0057] 1) First, 23 parts of magnesium peroxide powder, 7 parts of metal aluminum powder and 0.3 parts of honey are placed in a ball mill, neon gas is charged into the ball mill for protection and the speed is adjusted to 50r / min, and the ball milling is mixed for 2h, and then 3 parts of silicon nitride powder, 3 parts of metal silicon powder and 10 parts of activated alumina powder are added and the ball milling is continued for 1h. The material temperature is ensured to be ≤60°C by a cooling device during the ball milling process; the obtained mixture is taken out and added to a mixer, and then 36 parts of sintered spinel with a particle size of 3-6mm, 6 parts of sintered spinel with a particle size of 1-3mm, 8 parts of dead-burned magnesia with a particle size of <1mm, 4 parts of silicon carbide with a particle size of <1mm and 0.7 parts of honey are added, and the mixture is stirred at 45r / min for 40min to obtain a ramming material;
[0058] 2) Place the ramming material in a mold of 230mm×114mm×65mm, press it into bricks with a brick press, leave it to dry naturally for 24 hours after demoulding, then place it on magnesia sand, and use a flame spray gun to spray flames at fixed points to make the local temperature reach 1250℃ and maintain it for 8s, thereby initiating thermite reaction and achieving self-propagating overall sintering.
[0059] Comparative Example 1
[0060] The only difference between Comparative Example 1 and Example 1 is that the silicon nitride powder used is α-Si3N4.
[0061] Comparative Example 2
[0062] The difference between Comparative Example 2 and Example 1 is that the amount of magnesium peroxide powder is increased to 30 parts.
[0063] Comparative Example 3
[0064] The only difference between Comparative Example 3 and Example 1 is that the amount of metal aluminum powder is increased to 11 parts.
[0065] Comparative Example 4
[0066] The only difference between Comparative Example 4 and Example 2 is that silicon nitride powder and metallic silicon powder are not added, and the amount of silicon carbide with a particle size of less than 1 mm is increased to 14 parts.
[0067] Comparative Example 5
[0068] The only difference between Comparative Example 5 and Example 3 is that 8 parts of fused magnesia with a particle size of less than 1 mm are replaced by 8 parts of sintered spinel with a particle size of less than 1 mm.
[0069] Comparative Example 6
[0070] The only difference between Comparative Example 6 and Example 4 is that 10 parts of activated alumina powder are replaced by 10 parts of activated magnesia with the same particle size.
[0071] The bulk density, room temperature compressive strength, load softening temperature, thermal shock stability and other properties of the magnesium-aluminum spinel ramming materials of each embodiment and comparative example were tested with reference to GB / T 4513.6-2017. The results are shown in Table 1.
[0072] Table 1
[0073]
[0074]
[0075] Through the data of the magnesium-aluminum spinel fired bricks in Example 1, Example 2, Example 3, Example 4 and the comparative example, it can be known that the aluminothermic reaction sintered magnesium-aluminum spinel ramming mass provided by the present invention has a high bulk density and load softening temperature due to self-propagating overall sintering, and the thermal shock stability is significantly improved due to the addition of silicon carbide, and the self-propagating sintering obtains a compressive strength that is no less than that of the finished brick. Compared with magnesium-aluminum spinel bricks, the preparation of refractory bricks or ramming mass by this method does not require time and energy to burn products, saves energy consumed in the burning of refractory bricks, and can greatly improve production efficiency.
[0076] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. A self-propagating reaction sintered magnesia alumina spinel ramming mass, characterized in that: The invention comprises the following raw materials in parts by mass: 30-40 parts of spinel with a particle size of 3-6 mm, 5-15 parts of spinel with a particle size of 1-3 mm, 8-15 parts of magnesia with a particle size of less than 1 mm, 3-5 parts of silicon carbide with a particle size of less than 1 mm, 3-5 parts of silicon nitride powder, 2-5 parts of metallic silicon powder, 8-12 parts of activated alumina powder, 15-30 parts of magnesium peroxide powder, 5-10 parts of metallic aluminum powder, the sum of the parts by mass of the above raw materials is 100 parts, and 1-2 parts of liquid binder are added.
2. The self-propagating reaction sintered magnesia alumina spinel ramming material according to claim 1, characterized in that: The mass ratio of the magnesium peroxide powder to the metallic aluminum powder is (3-3.2):
1.
3. The self-propagating reaction sintered magnesia alumina spinel ramming material according to claim 1, characterized in that: The spinel is sintered spinel or fused spinel, and the sum of its Al2O3 and MgO content is ≥95%; the magnesia is dead-burned magnesia or fused magnesia, and the MgO content is ≥92%; the liquid binder is one or more of tung oil, phenolic resin, tar, maltose, and honey.
4. The self-propagating reaction sintered magnesia alumina spinel ramming material according to claim 1, characterized in that: The silicon carbide is black silicon carbide, with a SiC content of ≥98%; the silicon nitride powder is β-Si3N4, with a Si3N4 content of ≥98% and a particle size of 1 to 10 μm; the Si content of the metallic silicon powder is ≥98% and a particle size of 20 to 80 μm.
5. The self-propagating reaction sintered magnesia alumina spinel ramming mass according to claim 1, characterized in that: The Al2O3 content of the activated alumina powder is ≥99%, the particle size is ≤10 μm, and the median particle size D 50 The magnesium peroxide powder has a MgO2 content of ≥99.9%, a particle size of ≤10 μm, and a median particle size D 50 The Al content of the metal aluminum powder is greater than 99%, and the particle size is ≤50 μm.
6. A method for preparing a self-propagating reaction sintered magnesia-alumina spinel ramming mass according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) firstly, magnesium peroxide powder, metallic aluminum powder and a part of liquid binder are ball-milled and mixed once, then silicon nitride powder, metallic silicon powder and activated alumina powder are added and ball-milled for a second time, the obtained mixture is taken out and added into a blender, and then all the spinel, magnesia, silicon carbide and the remaining liquid binder are added and stirred evenly to obtain a ramming material; 2) The ramming material is formed or pressed into bricks through a mold, dried naturally after demoulding, and then locally heated with a flame spray gun or laser to induce a thermite reaction to achieve self-propagating overall sintering.
7. The method for preparing the self-propagating reaction sintered magnesia alumina spinel ramming mass according to claim 6, characterized in that: The local heating temperature is greater than 1250° C. and the time is 5 to 10 seconds.
8. The method for preparing the self-propagating reaction sintered magnesia alumina spinel ramming mass according to claim 6, characterized in that: The bulk density of the ramming material after sintering is 2.95-3.05 g / cm 3 , apparent porosity 14.5 ~ 16.5%, room temperature compressive strength 70 ~ 100MPa, load softening temperature > 1680 ℃, 1100 ℃ water-cooled thermal shock stability 20 ~ 25 times.
9. The method for preparing the self-propagating reaction sintered magnesia alumina spinel ramming mass according to claim 6, characterized in that: The ball milling is carried out under vacuum or inert atmosphere, the ball milling speed is 20-50 r / min, the first ball milling time is 1-2 hours, the second ball milling time is 2-3 hours, and the material temperature during the ball milling process is ≤60°C.
10. The method for preparing the self-propagating reaction sintered magnesia alumina spinel ramming mass according to claim 6, characterized in that: The liquid binder is added in two times, the first addition amount is 30-50% of the total mass, and the second addition amount is 50-70% of the total mass.
Citation Information
Patent Citations
Silicon carbide-magnesium aluminum spinel composite refractory material
CN107879753A
Silicon carbide-magnesium aluminate spinel-aluminum composite refractory material
CN111704466A
Carbon / magnesium aluminum spinel composite powder
CN107324796A
Composition for crushing
JP2003277181A
Coke oven blast furnace bottom repairing material
JP2018039939A